Silicon-carbon composite negative electrode material with elastic buffer structure and preparation method thereof
By using a silicon carbon composite material with elastic buffer structure in the negative electrode material of lithium -ion batteries, and using the elastic buffer layer and cover layer formed by modified carbon nanotubes, the existing materials expand The problem of stability has achieved improvement of comparison capacity, multiplier performance, and cycle stability.
Patent Information
- Application Number
- CN202411444066.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The existing carbon-covered porous silicon-carbon composite materials have specific capacity in the negative electrode materials of lithium-ion batteries, limited fast charging and fast release performance, and the inability to effectively buffer the volume expansion of porous silicon during lithium-embedding/deliquefaction, resulting in the electrode material The cycle stability is poor.
The silicon carbon composite negative material with elastic buffer structure is composed of porous silicon/silicon nanotimal pipes, carbon nanotimal pipe elastic buffer layers, and overwriting layers. The elastic buffer layer of the carbon nanotubes is aggregated and assembled by modified carbon nanotubes, forming a nano -pore structure of each other, and the volume expansion of cushioned porous silicon/silicon dioxide particles. The cover layer is composed of carbon or nitrogen doped to improve the electrical and stable solid electrolyte interface.
It improves the ratio capacity, multiplier performance, and cycle performance of silicon carbon composite lithium -ion batteries, effectively buffer the volume expansion of porous silicon in the process of lithium embedded lithium, and improves the stability and performance of the material.
Smart Images

Figure CN119029187B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium-ion batteries and relates to negative electrode materials for lithium-ion batteries, and more specifically, to a silicon-carbon composite negative electrode material with an elastic buffer structure and a preparation method thereof. Background Art
[0002] Since the 21st century, the world's energy problems have become increasingly prominent. The excessive use of non-renewable energy has triggered the global greenhouse effect, resulting in energy shortages and environmental degradation. In order to effectively respond to the energy crisis, the development of new energy materials and their industrial construction have received more and more attention. With the continuous development of new renewable energy sources such as solar energy, ocean energy, and wind energy, energy and environmental problems have been improved to a certain extent. However, due to the instability of natural conditions and the lack of related technologies, renewable energy will suffer a lot of losses during storage, making it difficult to cope with the working conditions of continuous energy supply. Therefore, researching and developing more effective energy storage technologies is one of the important links in achieving efficient development of the new energy industry.
[0003] Lithium-ion batteries are key energy storage devices in the fields of mobile communications, electric vehicles, and power grid peak regulation. They are widely used in various mobile communication devices due to their high charging and discharging efficiency, no heavy metal pollution, and long cycle life. With the deepening of energy transformation and the increase in the proportion of new renewable energy, it is urgent to develop more efficient energy storage lithium-ion batteries to meet the urgent demand for high-performance lithium-ion batteries in new energy vehicles and large-scale energy storage systems.
[0004] As the main energy storage body of lithium-ion batteries, the negative electrode is a key factor in determining the performance of lithium-ion batteries. An ideal negative electrode material should have the characteristics of high specific capacity, good lithium storage stability, high safety and environmental friendliness. Graphite materials have become the most commercialized negative electrode materials due to their advantages of low cost, high conductivity and high reversibility. However, the theoretical specific capacity of graphite is limited (372 mAh / g), which makes it difficult to meet the higher energy density requirements of the new generation of energy storage systems. Silicon has the highest theoretical specific capacity known in nature (forming Li at room temperature). 15 Si4, 3590 mAh / g; Li is formed at high temperature 22 Si5, 4200 mAh / g), lower potential to lithium (0.4 V vs. Li / Li +), rich in content and environmentally friendly, it is recognized as the most promising negative electrode material to replace traditional graphite. However, the current research and development of silicon-based negative electrode materials still faces the following urgent problems: silicon undergoes a huge volume change (300%~400%) during the lithium insertion / extraction process, which not only causes the negative electrode material to pulverize and fail due to the inability to withstand the huge mechanical stress, but also causes the continuous destruction and reconstruction of the solid electrolyte interface layer (SEI layer), resulting in the continuous consumption of lithium ions and reduced capacity.
[0005] CN 111211314 A discloses a carbon-coated porous silicon-carbon composite material and a preparation method thereof. The composite material is formed by uniformly coating carbon nanotubes on porous silicon. The preparation method comprises the following steps: S1, pickling and etching silicon alloy powder, adding carbon nanotubes before pickling or after etching to obtain a porous silicon mixed material; S2, configuring the porous silicon mixed material, a dispersant, and a slurry solvent into a slurry, dispersing the slurry by ball milling or sand milling, and drying the slurry to obtain a Si / SiOx-dispersant-carbon nanotube composite material; S3, placing the Si / SiOx-dispersant-carbon nanotube composite material in a high-temperature furnace, and carbonizing the slurry at 500-1200°C for 2-24 h under an inert gas atmosphere to obtain a Si / SiOx-C-carbon nanotube composite material; and S4, air-flow pulverizing the Si / SiOx-C-carbon nanotube composite material to obtain the composite material. The main function of introducing carbon nanotubes in this method is to provide a long-range conductive network. Although this can improve the conductivity of silicon negative electrode materials and avoid the loss of electronic conductivity of negative electrode materials during lithium insertion / delithiation, there are still the following shortcomings that need to be improved: (1) In step S1 of this method, silicon alloy powder is first added to hydrochloric acid for corrosion to remove metal elements, and then hydrofluoric acid is used for corrosion to remove silicon oxides. The pores obtained by etching are only located on the surface of the material. The pores are very few and discretely distributed, and no interconnected structure is formed. See the attached Figure 1 . On the one hand, such a pore structure is not conducive to the infiltration of the electrolyte into the interior of the porous silicon. The electrolyte has difficulty flowing in it, and it is difficult to achieve effective transmission of lithium ions in the porous silicon. On the other hand, such a pore structure makes the specific surface area of the porous silicon limited, and thus the contact area between the electrolyte and the porous silicon is limited, resulting in limited reaction activity of the electrode material. The above factors will limit the specific capacity, fast charge and discharge and other properties of the electrode material. (2) In the S2 step of this method, a dispersant is specially added for dispersion. Its purpose is to make the carbon nanotubes overlap each other on the surface of the porous silicon to form a conductive network structure, see its attached Figure 2The key to this method is that although the porous silicon will expand in volume during the lithium insertion / de-lithiation process, the conductive network formed is still effective after the porous silicon expands in volume, thereby avoiding the problem of loss of electronic conduction of silicon negative electrode materials during the lithium insertion / de-lithiation process. However, the conductive network formed by the overlapping carbon nanotubes itself cannot buffer the internal stress and volume expansion of the porous silicon inside during the charging and discharging process. Therefore, the material is still prone to pulverization and failure due to the huge volume change during the lithium ion insertion and de-insertion process, which is not conducive to improving the cycle stability of the negative electrode material. Summary of the invention
[0006] In view of the problems that existing carbon-coated porous silicon-carbon composite materials have limited specific capacity and fast charging and discharging performance, as well as the poor cycle stability of electrode materials caused by the inability to effectively buffer the volume expansion of porous silicon during lithium insertion / delithiation, the present invention provides a silicon-carbon composite negative electrode material with an elastic buffer structure and a preparation method thereof, so as to improve the specific capacity, rate performance and cycle performance of the silicon-carbon composite lithium-ion battery negative electrode material.
[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0008] A silicon-carbon composite negative electrode material with an elastic buffer structure, the composite negative electrode material consists of porous silicon / silicon dioxide particles, a carbon nanotube elastic buffer layer and a coating layer, the porous silicon / silicon dioxide particles consist of silicon particles and a silicon dioxide layer coating the silicon particles, the silicon / silicon dioxide particles have a uniform open nanoporous structure, the particle size of the silicon / silicon dioxide particles is in the micron level, the carbon nanotube elastic buffer layer is formed by modified carbon nanotubes that are mutually entangled and assembled, the carbon nanotube elastic buffer layer has a mutually interpenetrating nanopore structure, the thickness of the carbon nanotube elastic buffer layer is 100-300 nm, the modified carbon nanotube surface has hydroxyl and carboxyl functional groups, the coating layer consists of carbon or nitrogen-doped carbon; the carbon nanotube elastic buffer layer coats the porous silicon / silicon dioxide particles, the elastic buffer layer can buffer the volume expansion of the porous silicon / silicon dioxide particles during lithium insertion / delithiation, and the coating layer is coated outside the elastic buffer layer.
[0009] In the technical solution of the above-mentioned composite negative electrode material, in the composite negative electrode material, the sum of the contents of the carbon nanotube elastic buffer layer and the coating layer is 20 wt.% ~ 40 wt.%, and the remainder is porous silicon / silicon dioxide particles.
[0010] In the technical solution of the above composite negative electrode material, the thickness of the coating layer is 4-50 nm. The coating layer is composed of carbon or nitrogen-doped carbon, and mainly plays the following roles: the coating layer has excellent electron transmission ability and acts as a conductor, which is used to improve the conductivity of the composite negative electrode; the coating layer is located outside the elastic buffer layer, which can increase the bonding stability of the elastic buffer layer on the porous silicon / silicon dioxide particles and stabilize the solid electrolyte interface on the negative electrode surface; the coating layer is flexible and can coordinate the stress distribution inside the composite negative electrode material with the elastic buffer layer.
[0011] In the technical solution of the above-mentioned composite negative electrode material, when the coating material is nitrogen-doped carbon, the nitrogen content in the composite negative electrode material is 0.5 wt.%~5 wt.%.
[0012] In the technical solution of the composite negative electrode material, the particle size of the porous silicon / silicon dioxide particles is 1-30 μm, and the thickness of the silicon dioxide layer is 4-10 nm. The silicon dioxide layer is rigid and can inhibit the volume expansion of the porous silicon nanoparticles therein during the lithium insertion / extraction process.
[0013] In the technical solution of the composite negative electrode material, the content of Si element in the porous silicon / silicon dioxide particles is 80 wt.%~95 wt.%, and the balance is O element.
[0014] In the technical solution of the composite negative electrode material, the silicon / silicon dioxide particles and the carbon nanotube elastic buffer layer both have nanoscale pore structures, so that the pore sizes of the composite negative electrode material are respectively between 1 and 150 nm.
[0015] The present invention also provides a method for preparing the silicon-carbon composite negative electrode material having an elastic buffer structure, comprising the following steps:
[0016] (1) Preparation of porous silicon / silicon dioxide particles
[0017] The micron-sized silicon alloy particles are heat-treated at 550-1100° C. in an air atmosphere to completely oxidize the metal elements in the silicon alloy particles into metal oxides and replace the elemental silicon, and at the same time, the elemental silicon generated on the surface of the particles is oxidized into silicon dioxide, the heat-treated silicon alloy particles are immersed in an acidic solution that does not react with elemental silicon, the metal oxides are corroded and removed to form a uniform open nanoporous structure, and the obtained solid phase is washed and dried to obtain porous silicon / silicon dioxide particles;
[0018] (2) Activation and modification treatment
[0019] The porous silicon / silicon dioxide particles are added to a hexadecyltrimethylammonium bromide aqueous solution, stirred sufficiently, and the solid-liquid separation is performed, and the obtained solid phase is washed and dried to obtain activated porous silicon / silicon dioxide particles;
[0020] Immerse the carbon nanotubes in a mixture of HNO3 and H2SO4, fully react at 50-100°C to form functional groups including hydroxyl and carboxyl groups on the surface of the carbon nanotubes, separate the solid and the liquid, and obtain modified carbon nanotubes;
[0021] (3) Preparation of elastic buffer particles
[0022] The activated porous silicon / silicon dioxide particles are fully dispersed in water and the pH value is adjusted to 1-5 to obtain dispersion A; the modified carbon nanotubes are added into water and stirred at a speed of 60-600 rpm for 0.3-3 h to pre-assemble the modified carbon nanotubes in water to form modified carbon nanotube aggregates to obtain dispersion B; the dispersion A is added dropwise into the dispersion B and stirred for 5-10 h to assemble the modified carbon nanotube aggregates on the surface of the activated porous silicon / silicon dioxide particles to form an elastic buffer layer, and the solid-liquid separation is performed to obtain elastic buffer particles;
[0023] In this step, the amount of dispersion A and dispersion B is controlled so that the mass ratio of activated porous silicon / silicon dioxide particles to modified carbon nanotubes is (1-3): 1; the concentration of activated porous silicon / silicon dioxide particles in dispersion A is 2-6 g / L, and the concentration of modified carbon nanotubes in dispersion B is 1-5 g / L;
[0024] (4) Preparation of composite negative electrode materials
[0025] The elastic buffer particles are dispersed in water, and then monomers or polymer materials are added to form a reaction precursor solution. Reaction conditions are applied to polymerize the monomers and coat the surfaces of the elastic buffer particles, or to coat the surfaces of the elastic buffer particles with polymer materials. The solid-liquid separation is performed, and the obtained solid phase is washed and dried, and fully carbonized at 600-800°C under a protective gas atmosphere to obtain a composite negative electrode material.
[0026] In the technical solution of the above preparation method, the content of Si in the silicon alloy is 30 wt.% to 70 wt.%, and the silicon alloy is Mg-Si alloy, Ni-Si alloy or Fe-Si alloy. The silicon alloy can be prepared by itself or purchased directly from the market.
[0027] In the technical solution of the above preparation method, the particle size of the micron-sized silicon alloy particles is usually 1-30 μm.
[0028] In the reaction precursor solution of step (4) of the technical solution of the above preparation method, the mass ratio of the elastic buffer particles to the monomer or polymer material should be such that the thickness of the coating layer reaches 4 to 50 nm. Usually, the mass ratio of the elastic buffer particles to the monomer or polymer material is (2 to 100): 1. Usually, the concentration of the elastic buffer particles in the reaction precursor solution is 1 to 5 g / L.
[0029] Furthermore, in the technical solution of the above preparation method, the monomer in step (4) is dopamine or phenolic resin, and the polymer material is polyvinyl pyrrolidone or polypyrrole. When the polymer material is polyvinyl pyrrolidone or polypyrrole, the coating material formed by carbonization in step (4) is a carbon material; when the monomer is dopamine or phenolic resin, the coating material formed by carbonization in step (4) is nitrogen-doped carbon.
[0030] In the technical scheme of the above-mentioned preparation method, the step (4) of applying reaction conditions refers to providing appropriate conditions to allow the polymer material in the reaction precursor liquid to be coated on the surface of the elastic buffer particles, or to allow the monomers in the reaction precursor liquid to undergo polymerization reaction and the formed polymer to be coated on the surface of the elastic buffer particles. Generally, for polymer materials, the polymer material can be coated on the surface of the elastic buffer particles by stirring the reaction precursor liquid; for monomers, by applying conditions that can polymerize the monomers, the monomers can be polymerized to form polymers coated on the surface of the elastic buffer particles. For example, when the monomer is dopamine, the pH value of the reaction precursor liquid is adjusted to 7-9 by tris(hydroxymethyl)aminomethane, so that dopamine can be polymerized and form polydopamine coated on the surface of the elastic buffer particles.
[0031] In step (4) of the technical solution of the above preparation method, the protective gas is argon or nitrogen, and the carbonization time is preferably 2 to 3 hours.
[0032] In step (2) of the technical solution of the above-mentioned preparation method, the concentration of the aqueous solution of hexadecyltrimethylammonium bromide is 1 wt.%~10 wt.%; in the mixed solution of HNO3 and H2SO4, the concentration of HNO3 is 15 wt.%~60 wt.%, and the concentration of H2SO4 is 5 wt.%~30 wt.%.
[0033] In step (2) of the technical solution of the above preparation method, the porous silicon / silicon dioxide particles are added to a hexadecyltrimethylammonium bromide aqueous solution, stirred for 1 to 3 hours, and the solid-liquid separation is performed. The obtained solid phase is washed and dried to obtain activated porous silicon / silicon dioxide particles.
[0034] In step (2) of the technical solution of the above preparation method, the carbon nanotubes are immersed in a mixture of HNO3 and H2SO4, reacted at 50-100°C for 1-15 hours, and the solid-liquid separation is performed to obtain modified carbon nanotubes.
[0035] In step (1) of the technical solution of the above preparation method, the heat treatment time of the micron-sized silicon alloy particles at 550-1100°C in an air atmosphere should ensure that the metal elements in the silicon alloy particles are completely oxidized into metal oxides and the elemental silicon is replaced, and the elemental silicon generated on the surface of the particles is oxidized into a silicon dioxide layer of appropriate thickness (e.g., 4-10 nm). The silicon alloy particles can usually be heat treated at 550-1100°C in an air atmosphere for 10-80 h.
[0036] In step (1) of the technical solution of the above-mentioned preparation method, the acidic solution that does not react with elemental silicon is a hydrochloric acid solution, a sulfuric acid solution or a nitric acid solution, and the concentration of the acidic solution is 5 wt.%~60 wt.%.
[0037] The principles of the present invention are mainly as follows:
[0038] When micron-sized silicon alloy particles are heat treated at high temperature in air, the metal elements in the silicon alloy particles react with oxygen to generate metal oxides, displacing elemental silicon, and oxidizing the elemental silicon generated on the particle surface into a silicon dioxide layer of appropriate thickness (e.g., 4-10 nm). Since elemental silicon hardly reacts with acidic solutions other than hydrofluoric acid, the heat-treated alloy particles are immersed in an acidic solution without hydrofluoric acid to react, thereby corroding and removing the metal oxides, and the pores replace the original metal oxides. After being refined by grinding, silicon / silicon dioxide particles (i.e., porous silicon / silicon dioxide particles) with a uniform open nanoporous structure are obtained.
[0039] The porous silicon / silicon dioxide particles are activated by using an aqueous solution of hexadecyltrimethylammonium bromide to modify cationic functional groups on the surface of the porous silicon / silicon dioxide particles; the carbon nanotubes are modified by using an acid solution to form a large number of functional anionic energy groups such as hydroxyl and carboxyl groups on the surface of the carbon nanotubes; the modified carbon nanotubes usually tend to agglomerate, and in step (3), under appropriate stirring conditions, the modified carbon nanotubes are pre-assembled in water to form modified carbon nanotube aggregates of appropriate sizes, and then the activated porous silicon / silicon dioxide particle dispersion is added dropwise to the modified carbon nanotube aggregates, and the modified carbon nanotube aggregates are further assembled on the surface of the activated porous silicon / silicon dioxide particles (depending on the electrostatic interaction and hydrogen bonding between the cationic functional groups on the surface of the activated porous silicon / silicon dioxide particles and the anionic functional groups on the surface of the modified carbon nanotube aggregates) to form an elastic buffer layer covering the activated porous silicon / silicon dioxide particles, thereby obtaining elastic buffer particles. Since the elastic buffer layer is formed by a large number of modified carbon nanotubes intertwined and assembled, it contains a large number of interconnected nanoscale pores. At the same time, since the elastic buffer layer has a certain thickness (100-300 nm), it has good elasticity and can effectively buffer the volume expansion of the porous silicon / silicon dioxide particles in the process of lithium insertion / delithiation. The elastic buffer particles are dispersed in water, monomers or polymer materials are added to form a reaction precursor liquid, and reaction conditions are applied to polymerize the monomers and coat the surface of the elastic buffer particles, or the polymer materials are coated on the surface of the elastic buffer particles, and then carbonized under a protective gas atmosphere, and the polymer formed by the polymerization of the polymer material or monomers coating the elastic buffer particles is pyrolyzed, that is, a coating layer is formed on the surface of the elastic buffer particles, thereby obtaining the composite negative electrode material of the present invention.
[0040] The porous silicon / silicon dioxide nanoparticles in the composite negative electrode material provided by the present invention have an open nanoporous structure with uniform structure, and the carbon nanotube elastic buffer layer also has a large number of nanoscale pore structures. These rich pore structures are very conducive to the infiltration, circulation and efficient mass transfer of the electrolyte, and thus are conducive to the efficient transmission of lithium ions in the composite negative electrode material. The large number of pore structures make the composite negative electrode material have a high specific surface area, which can increase the contact between the electrolyte and the composite negative electrode material and improve the reaction activity of the composite negative electrode material. The above factors are conducive to improving the specific capacity, fast charging and discharging performance (rate performance) and cycle stability of the composite negative electrode material. The silicon dioxide layer coating the silicon nanoparticles as a rigid layer can inhibit the volume expansion of the silicon nanoparticles inside it during the lithium insertion / de-lithiation process. The modified carbon nanotube elastic buffer layer with a certain thickness (100-300 nm) and a porous structure can absorb the mechanical stress generated by the porous silicon / silicon dioxide particles during the lithium insertion / de-lithiation process, and buffer the volume expansion of the porous silicon / silicon dioxide particles during the lithium insertion / de-lithiation process. The coating layer located outside the elastic buffer particles is also flexible, which can buffer the volume expansion of the porous silicon / silicon dioxide particles during the lithium insertion / de-lithiation process, and coordinate the stress distribution inside the composite negative electrode material together with the elastic buffer layer, which is conducive to avoiding the problem of material pulverization failure caused by volume expansion during the lithium insertion / de-lithiation process, and improving the cycle performance of the negative electrode. At the same time, the coating layer has excellent electron transmission ability, plays a conductive role, and can improve the conductivity of the composite negative electrode. In addition, the coating of the elastic buffer layer by the coating layer can increase the binding stability of the elastic buffer layer on the porous silicon / silicon dioxide particles, stabilize the solid electrolyte interface on the negative electrode surface, and reduce the loss of lithium ions. The combined effect of the above multiple factors has effectively improved the specific capacity, rate performance and cycle stability of the composite negative electrode material provided by the present invention.
[0041] Compared with the prior art, the technical solution provided by the present invention produces the following beneficial technical effects:
[0042] 1. The present invention provides a silicon-carbon composite negative electrode material with an elastic buffer structure. The composite negative electrode material consists of porous silicon / silicon dioxide particles, a carbon nanotube elastic buffer layer and a coating layer. The porous silicon / silicon dioxide particles consist of silicon particles and a silicon dioxide layer coating the silicon particles. The silicon / silicon dioxide particles have a uniform open nanoporous structure. The particle size of the silicon / silicon dioxide particles is in the micron level. The carbon nanotube elastic buffer layer is assembled by mutually entangled and aggregated modified carbon nanotubes. The carbon nanotube elastic buffer layer has a mutually interpenetrating nanopore structure. The thickness of the carbon nanotube elastic buffer layer is 100-300 nm. The surface of the modified carbon nanotube has hydroxyl and carboxyl functional groups. The coating layer consists of carbon or nitrogen-doped carbon. The carbon nanotube elastic buffer layer coats the porous silicon / silicon dioxide particles. The elastic buffer layer can buffer the volume expansion of the porous silicon / silicon dioxide particles during lithium insertion / delithiation. The coating layer is coated outside the elastic buffer layer. Compared with the prior art (CN 111211314 A), the porous silicon / silicon dioxide particles of the present invention have a significantly richer pore structure, and the uniform open nanoporous structure thereon and the rich pore structure in the carbon nanotube elastic buffer layer are very conducive to the infiltration, circulation and efficient mass transfer of the electrolyte, and are conducive to the transmission of lithium ions in the composite negative electrode material. At the same time, it can increase the specific surface area of the composite negative electrode material, thereby increasing the contact between the electrolyte and the composite negative electrode material, and improving the reaction activity of the composite negative electrode material, which are all conducive to improving the specific capacity, fast charging and discharging performance and cycle stability of the composite negative electrode material. At the same time, compared with the prior art (CN 111211314 A), the carbon nanotube elastic buffer layer in the negative electrode material of the present invention has a certain thickness and the modified carbon nanotubes are densely entangled and aggregated with each other, which can absorb the mechanical stress generated by the porous silicon / silicon dioxide particles during the lithium insertion / de-lithiation process, and buffer the volume expansion of the porous silicon / silicon dioxide particles during the lithium insertion / de-lithiation process. The flexible coating layer located outside the elastic buffer particles can not only coordinate the stress distribution inside the composite negative electrode material with the elastic buffer layer, avoiding the problem of material pulverization failure caused by volume expansion during lithium insertion / de-lithiation, but also improve the conductivity of the composite negative electrode and increase the bonding stability of the elastic buffer layer on the porous silicon / silicon dioxide particles. Therefore, the composite negative electrode material of the present invention is effectively improved in specific capacity, rate performance and cycle stability compared with the prior art.
[0043] 2. The present invention has experimentally confirmed that the lithium-ion battery assembled based on the composite negative electrode of the present invention exhibits excellent electrochemical properties. In Example 1, at a charge and discharge current density of 0.1 C, it shows a high specific capacity and excellent capacity retention rate. The initial charge and discharge specific capacity can reach 1733.4 mAh / g and 4062.9 mAh / g. After 100 cycles, the capacity retention rate is 92.9%, and the coulombic efficiency is above 99.0%; at a current density of 0.4 C, it still has a reversible specific capacity of 633.0 mAh / g, showing high capacity, high stability cycle performance and good rate performance. In Example 4, after 9 weeks of cycling at a current density of 0.1 C, the charge specific capacity of the negative electrode is maintained at 758.07 mAh g -1 At the current density of 0.2~0.5 C, the change trend of the charge capacity and discharge capacity of the negative electrode is stable. After the current density changes from 0.5 C to 0.1 C, the charge capacity can quickly recover to 658.08 mAh g -1 , showing good rate performance.
[0044] 3. The present invention also provides a method for preparing the above-mentioned silicon-carbon composite negative electrode material with an elastic buffer structure. The method first uses low-cost micron-sized silicon alloy as a raw material to prepare silicon / silicon dioxide particles with a uniform open nanoporous structure. Compared with the prior art (CN 111211314 A), the present invention can reduce production costs while enhancing the mass transfer of the electrolyte, improving the transmission performance of lithium ions in the composite negative electrode material, and improving the reaction activity of the composite negative electrode material. On this basis, the present application utilizes modified carbon nanotube aggregates of appropriate sizes to assemble on the surface of porous silicon / silicon dioxide particles to form a carbon nanotube elastic buffer layer with a certain thickness and densely entangled and aggregated modified carbon nanotubes. Compared with the prior art (CN 111211314 A) in which carbon nanotubes are fully dispersed on the surface of porous silicon to form a long-range conductive network, the method of the present invention can effectively buffer the volume expansion of porous silicon / silicon dioxide particles during lithium insertion / delithiation, and avoid the problem of pulverization and failure of negative electrode materials during use. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 is the XRD spectrum of the Mg2Si alloy particles used in the examples.
[0046] Figure 2 is the EDS spectrum of the Mg2Si alloy particles used in the examples.
[0047] Figure 31 and 2 are SEM images and element distribution diagrams of the Mg2Si alloy particles used in the examples, wherein (a), (b), and (c) are SEM images and element distribution diagrams of Mg and Si, respectively.
[0048] Figure 4 is the XRD spectrum of the porous silicon / silicon dioxide particles prepared in Example 1.
[0049] Figure 5 This is the XPS spectrum of the porous silicon / silicon dioxide particles prepared in Example 1.
[0050] Figure 6 These are SEM images of the porous silicon / silicon dioxide particles prepared in Example 1, wherein (a) and (b) are at different magnifications.
[0051] Figure 7 This is the EDS spectrum of the porous silicon / silicon dioxide particles prepared in Example 1.
[0052] Figure 8 is a SEM image of the modified carbon nanotube aggregate in Example 1.
[0053] Fig. 9 This is the XRD spectrum of the composite negative electrode material prepared in Example 1.
[0054] Fig.10 These are SEM images of the composite negative electrode material prepared in Example 1, wherein (a) and (b) have different magnifications.
[0055] Fig.11 These are TEM images of the composite negative electrode material prepared in Example 1, wherein (a) and (b) have different magnifications.
[0056] Fig.12 1 is a nitrogen adsorption-desorption curve (Figure (a)) and a pore size distribution diagram (Figure (b)) of the composite negative electrode material prepared in Example 1.
[0057] Fig.13 This is the constant current charge and discharge performance curve of the lithium ion battery prepared in Example 1.
[0058] Fig.14 This is the rate performance curve of the negative electrode of the lithium ion battery prepared in Example 1.
[0059] Fig.15 This is the SEM image of the porous silicon material prepared in Comparative Example 1.
[0060] Fig.16 This is the constant current charge and discharge performance curve of the negative electrode of the lithium ion battery prepared in Example 2.
[0061] Fig.17This is the constant current charge and discharge performance curve of the negative electrode of the lithium ion battery prepared in Example 3.
[0062] Fig.18 is the XRD spectrum of the porous silicon / silicon dioxide particles prepared in Example 2.
[0063] Fig.19 This is the thermogravimetric curve of the composite negative electrode material prepared in Example 2.
[0064] Fig. 20 These are SEM images of the composite negative electrode material prepared in Example 2, wherein (a) and (b) have different magnifications.
[0065] Fig.21 is the XRD spectrum of the porous silicon / silicon dioxide particles prepared in Example 3.
[0066] Fig. 22 This is the EDS spectrum of the porous silicon / silicon dioxide particles prepared in Example 3.
[0067] Fig.23 3 is the XRD spectrum of the porous silicon / silicon dioxide particles prepared in Example 4.
[0068] Fig.24 This is the rate performance curve of the negative electrode of the lithium ion battery prepared in Example 4. DETAILED DESCRIPTION
[0069] The silicon-carbon composite negative electrode material with an elastic buffer structure and the preparation method thereof provided by the present invention are further described below through examples.
[0070] In the following examples and comparative examples, the Mg2Si alloy particles were purchased from Shanghai Nano Nano Technology Co., Ltd. Figure 1 is the XRD spectrum of Mg2Si alloy particles, Figure 2 It is the EDS spectrum of Mg2Si alloy particles. Figure 3 Figures (a), (b), and (c) are the SEM images and element distribution diagrams of Mg2Si alloy particles, respectively. The diagrams show that the particle size of the Mg2Si alloy particles does not exceed 30 μm, and the Mg and Si elements are evenly distributed.
[0071] In the following examples and comparative examples, the Ni-Si alloy is prepared by mixing Ni and Si and then ball milling, and the Fe-Si alloy is prepared by mixing Fe and Si and then ball milling.
[0072] In the following embodiments and comparative examples, the steps of assembling the lithium ion battery are as follows:
[0073] (1) The negative electrode material, conductive carbon black, polyacrylic acid (PAA) and polyvinyl alcohol (PVA) were mixed in a mass ratio of 60: 20: 10: 10, and the resulting mixture was added to deionized water and ultrasonicated for 15 min to disperse the various substances evenly to obtain a slurry. The resulting slurry was applied to the foamed copper with a scraper, flattened and dried to obtain a negative electrode sheet.
[0074] (2) Prepare fresh electrolyte: Mix ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) in a volume ratio of 1: 1: 1, then add fluoroethylene carbonate (FEC), vinylene carbonate (VC) and lithium hexafluorophosphate (LiPF6) and mix well to obtain an electrolyte. In the electrolyte, the concentration of LiPF6 is 1 mol / L, the concentration of FEC is 5 wt.%, and the concentration of VC is 1 wt.%.
[0075] (3) Using the negative electrode as the working electrode, the metal lithium sheet as the counter electrode, and microporous polypropylene as the separator, a CR2032 standard battery shell was selected to assemble the button-type lithium-ion half-cell in a glove box filled with argon gas and with water and oxygen content less than 0.1 ppm. After assembly, the battery was sealed with a hydraulic sealing machine to complete the assembly of the button-type battery. All button-type batteries were left to stand at 20 °C for 20 h before the electrochemical performance test to ensure that the electrolyte fully wetted the electrodes.
[0076] Example 1
[0077] In this embodiment, the steps for preparing a silicon-carbon composite negative electrode material having an elastic buffer structure are as follows:
[0078] (1) Preparation of porous silicon / silicon dioxide particles
[0079] Mg2Si alloy particles were placed in a muffle furnace, heated to 550 °C in an air atmosphere and kept at this temperature for 20 hours for heat treatment, so that the magnesium element in the Mg2Si alloy particles was completely oxidized into magnesium oxide and replaced with elemental silicon. At the same time, the elemental silicon generated on the surface of the particles was oxidized into silicon dioxide. After being taken out and naturally cooled in the air, they were immersed in a hydrochloric acid solution with a concentration of 5 wt.%, corroded at room temperature for 10 hours to remove magnesium oxide, and the solid-liquid separation was carried out. The obtained solid phase was repeatedly washed with deionized water and ethanol, vacuum dried, and fully ground to obtain porous silicon / silicon dioxide particles.
[0080] Figures 4 to 7 The following are the XRD spectrum, XPS spectrum, SEM spectrum and EDS spectrum of the porous silicon / silicon dioxide particles prepared in this embodiment. Figures 4 to 7 It can be seen that the porous silicon / silicon dioxide particles are composed of Si phase and SiO2 phase. The broad peak at about 103.5 eV in the XPS spectrum corresponds to Si4+ The broad peak located at about 99.5 eV corresponds to the characteristic peak of zero-valent silicon, which further confirms the presence of silicon and silicon dioxide in the material. The content of Si element in the porous silicon / silicon dioxide particles is 94.18 wt.%, and the content of O element is 5.82 wt.%. The porous silicon / silicon dioxide particles have a uniform open nanoporous structure.
[0081] (2) Activation and modification treatment
[0082] The porous silicon / silicon dioxide particles were added to a 3.5 wt.% hexadecyltrimethylammonium bromide (CTAB) aqueous solution, stirred for reaction for 1 h, and the solid-liquid separation was performed. The obtained solid phase was repeatedly washed with deionized water and ethanol and dried to obtain activated porous silicon / silicon dioxide particles.
[0083] The carbon nanotubes were immersed in a mixture of HNO3 and H2SO4, wherein the concentration of HNO3 was 49.6 wt.%, and the concentration of H2SO4 was 27.0 wt.%, and the mixture was reacted in a water bath at 80°C for 1.5 h, and the solid-liquid separation was performed to obtain modified carbon nanotubes.
[0084] (3) Preparation of elastic buffer particles
[0085] The activated porous silicon / silicon dioxide particles were added to deionized water and ultrasonically dispersed for 10 min, and then the pH value was adjusted to 1 with hydrochloric acid to obtain a dispersion A with a concentration of 6 g / L. The modified carbon nanotubes were added to water and stirred at a speed of 200 rpm for 2 h to pre-assemble the modified carbon nanotubes in water to form modified carbon nanotube aggregates to obtain dispersion B. The concentration of the modified carbon nanotubes in dispersion B was 2 g / L. According to the mass ratio of activated porous silicon / silicon dioxide particles to modified carbon nanotubes of 3:1, dispersion A was added dropwise to dispersion B. After the addition was completed, ultrasonic dispersion was performed for 10 min, and then stirred at room temperature for 10 h to allow the modified carbon nanotube aggregates to assemble on the surface of the activated porous silicon / silicon dioxide particles to form an elastic buffer layer, and solid-liquid separation was performed to obtain elastic buffer particles.
[0086] Dispersion liquid B was added dropwise onto the copper grid, and the aggregation state of the modified carbon nanotube aggregates was observed by SEM. Figure 8 As shown, it can be seen from the figure that the modified carbon nanotubes are entangled and assembled to form aggregates during the stirring process.
[0087] (4) Preparation of composite negative electrode materials
[0088] The elastic buffer particles were added to deionized water and ultrasonically dispersed for 10 min, and tris(hydroxymethyl)aminomethane was added to adjust the pH value to 7 to obtain a dispersion of elastic buffer particles with a concentration of 2 g / L. According to the mass ratio of elastic buffer particles to dopamine hydrochloride of 2:1, dopamine hydrochloride was added to the dispersion of elastic buffer particles to make its concentration in the dispersion 1 g / L, and the reaction was stirred for 24 h to polymerize dopamine hydrochloride to form polydopamine coating the elastic buffer particles, and the solid-liquid separation was performed. The obtained solid phase was washed with deionized water, vacuum dried, loaded into a ceramic crucible and placed in a tubular furnace. Under the condition of continuous introduction of argon as a protective atmosphere, the temperature was increased from room temperature to 800 °C at a rate of 5 °C / min and kept at this temperature for 3 h for carbonization, and then cooled to room temperature with the furnace to obtain the obtained product.
[0089] Fig. 9 is the XRD spectrum of the composite negative electrode material prepared in this embodiment, Fig. 9 It shows that the composite negative electrode material contains Si phase and SiO2 phase. Fig.10 The SEM images of the composite negative electrode material prepared in this example, wherein (a) and (b) have different magnifications. Fig.10 Figure (a) shows that the porous silicon / silicon dioxide particles are coated with a carbon nanotube elastic buffer layer, and the thickness of the carbon nanotube elastic buffer layer is about 100 nm. Fig.10 Figure (b) shows that in the carbon nanotube elastic buffer layer, the modified carbon nanotubes are densely entangled and aggregated with each other. Fig.11 TEM images of the composite negative electrode material prepared in this example, wherein (a) and (b) have different magnifications. Fig.11 It can be seen that the thickness of the coating layer is 4~8 nm, and the thickness of the silicon dioxide layer is 4~6 nm. By calibrating the interplanar spacing of the porous silicon / silicon dioxide particles in the high-resolution TEM image, the crystal planes to which they belong are determined. 0.314 nm corresponds to the (111) crystal plane of Si, and 0.192 nm corresponds to the (220) crystal plane of Si. The specific surface area of the composite negative electrode material is determined by the BET method, as shown in Fig.12 As shown in Figure (a), the result is about 139.07 m 2 / g, the pore volume of the composite negative electrode material was measured by the single-point method, and the result was about 0.61 cm 3 / g, the pore size distribution of the composite negative electrode material is determined by the BJH method, such as Fig.12 As shown in Figure (b), the pore size distribution is between 1 and 140 nm, and is mainly concentrated between 40 and 60 nm.
[0090] The composite negative electrode material prepared in this example was assembled into a lithium-ion battery. A constant current charge and discharge tester model NEWARE BTS-610 was used to test the cycle performance of the lithium-ion battery. The test voltage range was 0.01~1.5 V (vs. Li / Li + ), the test temperature is 15~25℃.
[0091] The cycle performance test results of the lithium ion battery prepared in this example are as follows: Fig.13 As shown by Fig.13 It can be seen that at a charge and discharge current density of 0.1C, the negative electrode material shows high specific capacity and coulombic efficiency. The first charge and discharge specific capacities are 1733.4 mAh / g and 4062.9 mAh / g, respectively, and the first coulombic efficiency is 42.7%. The capacity loss is mainly related to the formation of the SEI film. After 100 cycles, the charge specific capacity can still be maintained at 1610.5 mAh / g, the capacity retention rate is 92.9%, and the coulombic efficiency is above 99.0%, with high reversible capacity and capacity retention rate. The rate performance test results are as follows Fig.14 As shown by Fig.14 It can be seen that when the current density is 0.4 C, it still has a reversible specific capacity of 633.0 mAh / g, which has good rate performance.
[0092] Comparative Example 1
[0093] In this comparative example, the Mg2Si alloy particles used in Example 1 were used as raw materials, and the porous silicon material was prepared by the method in Example 9 of CN 111211314 A, as follows:
[0094] 1 part by mass of Mg2Si alloy particles was added to 7.5 parts by mass of 6 mol / L hydrochloric acid, reacted at 90 °C for 24 h to remove metal elements, washed with deionized water until neutral, and vacuum dried at 80 °C for 24 h. The obtained product was added to 7.5 parts by mass of 1 mol / L hydrofluoric acid for etching, reacted at room temperature for 6 h, and washed with deionized water until neutral to obtain a porous silicon material, the SEM image of which is shown in FIG. Fig.15 shown.
[0095] Depend on Fig.15 It can be seen that the porous silicon material prepared in this comparative example only has a small amount of discretely distributed pore structures on the surface, and these pore structures are independent of each other and do not penetrate each other. Combining Example 1 and Comparative Example 1, it can be seen that the method of first thermally oxidizing the silicon alloy particles and then corroding them in Example 1 can effectively improve the porosity of the porous silicon material, and can make the pore structures penetrate each other to form a uniform open nanoporous structure.
[0096] Comparative Example 2
[0097] In this comparative example, the porous silicon / silicon dioxide particles prepared in step (1) of Example 1 were assembled into a lithium ion battery, and the cycle performance of the lithium ion battery was tested in the same manner as in Example 1.
[0098] The constant current charge and discharge performance curve of the negative electrode of the lithium ion battery prepared in this comparative example is as follows: Fig.16 As shown by Fig.16 It can be seen that at a charge and discharge current density of 0.1 C, the reversible specific capacity of the first cycle is 1817.5 mAh / g, and the first coulombic efficiency is 40.9%. After 50 cycles, the reversible specific capacity is 446.5 mAh / g, and the capacity retention rate is 24.6%.
[0099] Comparative Example 3
[0100] In this embodiment, the elastic buffer particles prepared in step (3) of embodiment 1 are assembled into a lithium ion battery, and the cycle performance of the lithium ion battery is tested in the same manner as in embodiment 1.
[0101] The constant current charge and discharge performance curve of the negative electrode of the lithium ion battery prepared in this comparative example is as follows: Fig.17 As shown by Fig.17 It can be seen that at a charge and discharge current density of 0.1 C, the reversible specific capacity of the first week is 2232.5 mAh / g, and the first coulombic efficiency is 75.4%. After 50 cycles, the reversible specific capacity is 1358.9 mAh / g, and the capacity retention rate is 60.8%. It has a higher capacity, which is attributed to the higher silicon content in the electrode. However, its cycle stability is poor, and the overall capacity shows a very obvious downward trend, making it difficult to use for a long time.
[0102] Combining Example 1 and Comparative Examples 2 and 3, it can be seen that, compared with porous silicon / silicon dioxide particles and elastic buffer particles, the negative electrode prepared with the composite negative electrode material of the present invention has better cycle performance.
[0103] Example 2
[0104] In this embodiment, the steps for preparing a silicon-carbon composite negative electrode material having an elastic buffer structure are as follows:
[0105] (1) Preparation of porous silicon / silicon dioxide particles
[0106] The operation is basically the same as step (1) of Example 1, except that the heat treatment temperature is 1100°C, the holding time is 10 h, and the sample is immersed in a 10 wt.% hydrochloric acid solution and corroded at room temperature for 10 h to remove magnesium oxide.
[0107] Fig.18 is the XRD spectrum of the porous silicon / silicon dioxide particles prepared in this embodiment. Fig.18 It can be seen that the porous silicon / silicon dioxide particles are composed of Si phase and SiO2 phase.
[0108] (2) Activation and modification treatment
[0109] The operation is the same as step (2) of Example 1.
[0110] (3) Preparation of elastic buffer particles
[0111] The activated porous silicon / silicon dioxide particles were added to deionized water and ultrasonically dispersed for 10 min, and then the pH value was adjusted to 5 with hydrochloric acid to obtain a dispersion A with a concentration of 4 g / L. The modified carbon nanotubes were added to water and stirred at a speed of 60 rpm for 3 h to pre-assemble the modified carbon nanotubes in water to form modified carbon nanotube aggregates to obtain dispersion B. The concentration of modified carbon nanotubes in dispersion B was 2 g / L. According to the mass ratio of activated porous silicon / silicon dioxide particles to modified carbon nanotubes of 2:1, dispersion A was added dropwise to dispersion B. After the addition was completed, ultrasonic dispersion was performed for 10 min, and then stirred in a 100 ℃ water bath environment for 5 h to assemble the modified carbon nanotube aggregates on the surface of the activated porous silicon / silicon dioxide particles to form an elastic buffer layer, and solid-liquid separation was performed to obtain elastic buffer particles.
[0112] (4) Preparation of composite negative electrode materials
[0113] The elastic buffer particles were added to deionized water and ultrasonically dispersed for 10 min, and tris(hydroxymethyl)aminomethane was added to adjust the pH value to 9 to obtain a dispersion of elastic buffer particles with a concentration of 2 g / L. According to the mass ratio of elastic buffer particles to dopamine hydrochloride of 100:1, dopamine hydrochloride was added to the dispersion of elastic buffer particles to make its concentration in the dispersion 0.02 g / L, and the reaction was stirred for 24 h to polymerize dopamine hydrochloride to form polydopamine coating the elastic buffer particles, and the solid-liquid separation was performed. The obtained solid phase was washed with deionized water, vacuum dried, loaded into a ceramic crucible and placed in a tubular furnace. Under the condition of continuous introduction of argon as a protective atmosphere, the temperature was increased from room temperature to 600 °C at a rate of 5 °C / min and kept at this temperature for 2 h for carbonization, and then cooled to room temperature with the furnace to obtain the obtained product.
[0114] Fig.19 3 is the thermogravimetric curve of the composite negative electrode material prepared in this embodiment. It can be seen from the figure that the mass of the composite negative electrode material decreases rapidly between 350 and 650 °C, corresponding to the decomposition of carbon in the air, proving that the carbon content in the composite negative electrode material is about 32.34 wt.%. Fig. 20 The SEM images of the composite negative electrode material prepared in this embodiment, wherein (a) and (b) are at different magnifications. Fig. 20It can be seen that the porous silicon / silicon dioxide particles are coated by the carbon nanotube elastic buffer layer, and the modified carbon nanotubes in the carbon nanotube elastic buffer layer are densely entangled and aggregated with each other.
[0115] Example 3
[0116] In this embodiment, the steps for preparing a silicon-carbon composite negative electrode material having an elastic buffer structure are as follows:
[0117] (1) Preparation of porous silicon / silicon dioxide particles
[0118] The operation of this step is basically the same as step (1) of Example 1, except that the holding time during the heat treatment is 80 h. Figures 21 and 22 is the XRD spectrum and EDS spectrum of the porous silicon / silicon dioxide particles prepared in this embodiment. Figures 21 and 22 It can be seen that the porous silicon / silicon dioxide particles are composed of Si phase and SiO2 phase, in which the content of Si element is 89.31 wt.%, and the content of O element is 10.69 wt.%.
[0119] (2) Activation and modification treatment
[0120] The porous silicon / silicon dioxide particles were added to a CTAB aqueous solution with a concentration of 3.5 wt.%, stirred for reaction for 1 h, and the solid-liquid separation was performed. The obtained solid phase was repeatedly washed with deionized water and ethanol and dried to obtain activated porous silicon / silicon dioxide particles.
[0121] The carbon nanotubes were immersed in a mixture of HNO3 and H2SO4, wherein the concentration of HNO3 was 49.6 wt.%, and the concentration of H2SO4 was 27.0 wt.%, and the mixture was reacted in a water bath at 50°C for 10 h, and the solid-liquid separation was performed to obtain modified carbon nanotubes.
[0122] (3) Preparation of elastic buffer particles
[0123] The operation of this step is the same as step (3) of Example 1.
[0124] (4) Preparation of composite negative electrode materials
[0125] The elastic buffer particles were added to deionized water and ultrasonically dispersed for 10 min, and sodium hydroxide solution was added to adjust the pH value to 7 to obtain a dispersion of elastic buffer particles with a concentration of 2 g / L. According to the mass ratio of elastic buffer particles to phenolic resin of 20: 1, phenolic resin was added to the dispersion of elastic buffer particles to make its concentration in the dispersion 0.1 g / L, and the reaction was stirred for 24 h to polymerize the phenolic resin to form a polymer coating the elastic buffer particles, and the solid-liquid separation was performed. The obtained solid phase was washed with deionized water, vacuum dried, loaded into a ceramic crucible and placed in a tubular furnace. Under the condition of continuous introduction of argon as a protective atmosphere, the temperature was increased from room temperature to 700 °C at a rate of 5 °C / min and kept at this temperature for 2 h for carbonization, and then cooled to room temperature with the furnace to obtain the obtained product.
[0126] Example 4
[0127] In this embodiment, the steps for preparing a silicon-carbon composite negative electrode material having an elastic buffer structure are as follows:
[0128] (1) Preparation of porous silicon / silicon dioxide particles
[0129] The operation is basically the same as step (1) of Example 1, except that the heat treatment is carried out for 60 h and the sample is immersed in a 5 wt.% hydrochloric acid solution and corroded at 100 °C for 1.5 h to remove magnesium oxide.
[0130] Fig.23 is the XRD spectrum of the porous silicon / silicon dioxide particles prepared in this embodiment. Fig.23 It can be seen that the porous silicon / silicon dioxide particles are composed of Si phase and SiO2 phase.
[0131] (2) Activation and modification treatment
[0132] The operation is the same as step (2) of Example 1.
[0133] (3) Preparation of elastic buffer particles
[0134] The operation is the same as step (3) of Example 1.
[0135] (4) Preparation of composite negative electrode materials
[0136] The elastic buffer particles were added to deionized water and ultrasonically dispersed for 10 min to obtain a dispersion of elastic buffer particles with a concentration of 5 g / L. According to the mass ratio of elastic buffer particles to polypyrrole of 100:1, polypyrrole was added to the dispersion of elastic buffer particles to make the concentration in the dispersion 0.05 g / L, and the reaction was stirred for 24 h to make polypyrrole coat the elastic buffer particles, and the solid-liquid separation was performed. The obtained solid phase was washed with deionized water and vacuum dried. The product obtained by vacuum drying was loaded into a ceramic crucible and placed in a tubular furnace. Under the condition of continuous introduction of argon as a protective atmosphere, the temperature was increased from room temperature to 750 ℃ at a rate of 5 ℃ / min and kept at this temperature for 2 h for carbonization, and then cooled to room temperature with the furnace to obtain the product.
[0137] The composite negative electrode material prepared in this example was assembled into a lithium-ion battery, and the rate performance of the lithium-ion battery was tested using a constant current charge and discharge tester of model NEWARE BTS-610. The test voltage range was 0.01-1.5 V (vs. Li / Li + ), the test temperature is 15~25℃.
[0138] The rate performance curve of the negative electrode of the lithium ion battery prepared in this embodiment is as follows: Fig.24 As shown. Fig.24 It can be seen that after 9 cycles at a current density of 0.1C, the charge capacity of the negative electrode remains at 758.07 mAh g -1 , which is lower than the specific capacity in Example 1, which is attributed to the higher mass ratio of carbon materials in the negative electrode. Although the use of carbon materials will affect the lithium storage capacity to a certain extent, its excellent conductivity and more stable SEI layer on the surface can enhance the cycle stability of the negative electrode. At a current density of 0.2~0.5 C, the change trend of the charge specific capacity and discharge specific capacity of the negative electrode is more stable than that in Example 1. Moreover, after the current density changes from 0.5 C to 0.1 C, the charge specific capacity can be quickly restored to 658.08 mAh g -1 , indicating that the negative electrode has good rate performance.
[0139] Example 5
[0140] In this embodiment, the steps for preparing a silicon-carbon composite negative electrode material having an elastic buffer structure are as follows:
[0141] (1) Preparation of porous silicon / silicon dioxide particles
[0142] Fe-Si alloy particles with a Si content of 30 wt.% were placed in a muffle furnace, heated to 550 °C in an air atmosphere and kept at this temperature for 20 h for heat treatment, the iron element in the Fe-Si alloy particles was oxidized into iron oxide, and the silicon on the surface of the Fe-Si alloy particles was oxidized into silicon dioxide. After being taken out and naturally cooled in the air, they were immersed in a hydrochloric acid solution with a concentration of 10 wt.%, corroded at room temperature for 10 h to remove iron oxide, and the solid-liquid separation was carried out. The obtained solid phase was repeatedly washed with deionized water and ethanol, vacuum dried, and fully ground to obtain porous silicon / silicon dioxide particles.
[0143] (2) Activation and modification treatment
[0144] The porous silicon / silicon dioxide particles were added to a 1 wt.% CTAB aqueous solution, stirred for reaction for 3 h, and the solid-liquid separation was performed. The obtained solid phase was repeatedly washed with deionized water and ethanol and dried to obtain activated porous silicon / silicon dioxide particles.
[0145] The carbon nanotubes were immersed in a mixture of HNO3 and H2SO4, wherein the concentration of HNO3 was 49.6 wt.%, and the concentration of H2SO4 was 27.0 wt.%, and the mixture was reacted in a water bath at 100°C for 1 h, and the solid-liquid separation was performed to obtain modified carbon nanotubes.
[0146] (3) Preparation of elastic buffer particles
[0147] The activated porous silicon / silicon dioxide particles were added to deionized water and ultrasonically dispersed for 10 min, and then the pH value was adjusted to 5 with hydrochloric acid to obtain a dispersion A with a concentration of 6 g / L. The modified carbon nanotubes were added to water and stirred at a speed of 600 rpm for 0.3 h to pre-assemble the modified carbon nanotubes in water to form modified carbon nanotube aggregates to obtain dispersion B. The concentration of the modified carbon nanotubes in dispersion B was 2 g / L. According to the mass ratio of activated porous silicon / silicon dioxide particles to modified carbon nanotubes of 3:1, dispersion A was added dropwise to dispersion B. After the addition was completed, ultrasonic dispersion was performed for 10 min, and then stirred at room temperature for 10 h to assemble the modified carbon nanotube aggregates on the surface of the activated porous silicon / silicon dioxide particles to form an elastic buffer layer, and solid-liquid separation was performed to obtain elastic buffer particles.
[0148] (4) Preparation of composite negative electrode materials
[0149] The elastic buffer particles were added to deionized water and ultrasonically dispersed for 10 min to obtain a dispersion of elastic buffer particles with a concentration of 2 g / L. Phenolic resin was added to the dispersion of elastic buffer particles according to a mass ratio of 5:1 between the elastic buffer particles and the phenolic resin so that the concentration in the dispersion was 0.4 g / L, and the mixture was stirred for 24 h to polymerize the phenolic resin to form a polymer coating the elastic buffer particles. The solid-liquid separation was performed, and the obtained solid phase was washed with deionized water, vacuum dried, loaded into a ceramic crucible and placed in a tubular furnace. Under the condition of continuous introduction of argon as a protective atmosphere, the temperature was increased from room temperature to 800 °C at a rate of 5 °C / min and kept at this temperature for 2 h for carbonization, and then cooled to room temperature with the furnace to obtain the obtained product.
[0150] Example 6
[0151] In this embodiment, the steps for preparing a silicon-carbon composite negative electrode material having an elastic buffer structure are as follows:
[0152] (1) Preparation of porous silicon / silicon dioxide particles
[0153] Fe-Si alloy particles with a Si content of 40 wt.% were placed in a muffle furnace, heated to 700 °C in an air atmosphere and kept at this temperature for 20 h for heat treatment, so that the iron element in the Fe-Si alloy particles was oxidized into iron oxide, and the silicon on the surface of the Fe-Si alloy particles was oxidized into silicon dioxide. After being taken out and naturally cooled in the air, they were immersed in a nitric acid solution with a concentration of 15 wt.%, and corroded at room temperature for 10 h to remove iron oxide. The solid-liquid separation was carried out, and the obtained solid phase was repeatedly washed with deionized water and ethanol, vacuum dried, and fully ground to obtain porous silicon / silicon dioxide particles.
[0154] (2) Activation and modification treatment
[0155] The porous silicon / silicon dioxide particles were added to a 10 wt.% CTAB aqueous solution, stirred for reaction for 1 h, and the solid-liquid separation was performed. The obtained solid phase was repeatedly washed with deionized water and ethanol and dried to obtain activated porous silicon / silicon dioxide particles.
[0156] The carbon nanotubes were immersed in a mixture of HNO3 and H2SO4, wherein the concentration of HNO3 was 49.6 wt.%, and the concentration of H2SO4 was 27.0 wt.%, and the mixture was reacted in a water bath at 50°C for 10 h, and the solid-liquid separation was performed to obtain modified carbon nanotubes.
[0157] (3) Preparation of elastic buffer particles
[0158] The activated porous silicon / silicon dioxide particles were added to deionized water and ultrasonically dispersed for 10 min, and then the pH value was adjusted to 1 with hydrochloric acid to obtain a dispersion A with a concentration of 2 g / L. The modified carbon nanotubes were added to water and stirred at a speed of 100 rpm for 2.5 h to pre-assemble the modified carbon nanotubes in water to form modified carbon nanotube aggregates to obtain dispersion B, and the concentration of the modified carbon nanotubes in dispersion B was 2 g / L. According to the mass ratio of activated porous silicon / silicon dioxide particles to modified carbon nanotubes of 1:1, dispersion A was added dropwise to dispersion B, and ultrasonically dispersed for 10 min after the addition was completed, and then stirred at room temperature for 10 h to assemble the modified carbon nanotube aggregates on the surface of the activated porous silicon / silicon dioxide particles to form an elastic buffer layer, and solid-liquid separation was performed to obtain elastic buffer particles.
[0159] (4) Preparation of composite negative electrode materials
[0160] The elastic buffer particles were added to deionized water and ultrasonically dispersed for 10 min, and the pH value was adjusted to 7 to obtain a dispersion of elastic buffer particles with a concentration of 1 g / L. Polypyrrole was added to the dispersion of elastic buffer particles at a mass ratio of 2:1 to make the concentration in the dispersion 0.5 g / L, and the reaction was stirred for 24 h to make the polypyrrole coat the elastic buffer particles, and the solid-liquid separation was performed. The obtained solid phase was washed with deionized water, vacuum dried, loaded into a ceramic crucible and placed in a tubular furnace. Under the condition of continuous introduction of argon as a protective atmosphere, the temperature was increased from room temperature to 800 °C at a rate of 5 °C / min and kept at this temperature for 2 h for carbonization, and then cooled to room temperature with the furnace to obtain the obtained product.
[0161] Example 7
[0162] In this embodiment, the steps for preparing a silicon-carbon composite negative electrode material having an elastic buffer structure are as follows:
[0163] (1) Preparation of porous silicon / silicon dioxide particles
[0164] Fe-Si alloy particles with a Si content of 50 wt.% were placed in a muffle furnace, heated to 600 °C in an air atmosphere and kept at this temperature for 20 h for heat treatment, the iron element in the Fe-Si alloy particles was oxidized into iron oxide, and the silicon on the surface of the Fe-Si alloy particles was oxidized into silicon dioxide. After being taken out and naturally cooled in the air, they were immersed in a nitric acid solution with a concentration of 60 wt.%, corroded at room temperature for 10 h to remove iron oxide, and the solid-liquid separation was carried out. The obtained solid phase was repeatedly washed with deionized water and ethanol, vacuum dried, and fully ground to obtain porous silicon / silicon dioxide particles.
[0165] (2) Activation and modification treatment
[0166] The porous silicon / silicon dioxide particles were added to a CTAB aqueous solution with a concentration of 3.5 wt.%, stirred for reaction for 1 h, and the solid-liquid separation was performed. The obtained solid phase was repeatedly washed with deionized water and ethanol and dried to obtain activated porous silicon / silicon dioxide particles.
[0167] The carbon nanotubes were immersed in a mixture of HNO3 and H2SO4, wherein the concentration of HNO3 was 49.6 wt.%, and the concentration of H2SO4 was 27.0 wt.%, and the mixture was reacted in a water bath at 50°C for 10 h, and the solid-liquid separation was performed to obtain modified carbon nanotubes.
[0168] (3) Preparation of elastic buffer particles
[0169] The operation is the same as step (3) of Example 6.
[0170] (4) Preparation of composite negative electrode materials
[0171] The elastic buffer particles were added to deionized water and ultrasonically dispersed for 10 min, and the pH value was adjusted to 9 to obtain a dispersion of elastic buffer particles with a concentration of 1 g / L. Polyvinyl pyrrolidone was added to the dispersion of elastic buffer particles at a mass ratio of 100:1 to make the concentration in the dispersion 0.01 g / L, and the reaction was stirred for 24 h to coat the elastic buffer particles with polyvinyl pyrrolidone. The solid-liquid separation was performed, and the obtained solid phase was washed with deionized water, vacuum dried, loaded into a ceramic crucible and placed in a tubular furnace. Under the condition of continuous introduction of argon as a protective atmosphere, the temperature was increased from room temperature to 600 °C at a rate of 5 °C / min and kept at this temperature for 2 h for carbonization, and then cooled to room temperature with the furnace to obtain the obtained product.
[0172] Example 8
[0173] In this embodiment, the steps for preparing a silicon-carbon composite negative electrode material having an elastic buffer structure are as follows:
[0174] (1) Preparation of porous silicon / silicon dioxide particles
[0175] Ni-Si alloy particles with a Si content of 70 wt.% were placed in a muffle furnace, heated to 550 °C in an air atmosphere and kept at this temperature for 20 h for heat treatment, so that the iron element in the Ni-Si alloy particles was oxidized into nickel oxide, and the silicon on the surface of the Ni-Si alloy particles was oxidized into silicon dioxide. After being taken out and naturally cooled in the air, they were immersed in a sulfuric acid solution with a concentration of 5 wt.%, and corroded at room temperature for 24 h to remove nickel oxide. The solid-liquid separation was carried out, and the obtained solid phase was repeatedly washed with deionized water and ethanol, vacuum dried, and fully ground to obtain porous silicon / silicon dioxide particles.
[0176] (2) Activation and modification treatment
[0177] The porous silicon / silicon dioxide particles were added to a CTAB aqueous solution with a concentration of 3.5 wt.%, stirred for reaction for 1 h, and the solid-liquid separation was performed. The obtained solid phase was repeatedly washed with deionized water and ethanol and dried to obtain activated porous silicon / silicon dioxide particles.
[0178] The carbon nanotubes were immersed in a mixture of HNO3 and H2SO4, wherein the concentration of HNO3 was 60 wt.%, and the concentration of H2SO4 was 5.0 wt.%, and the mixture was reacted in a water bath at 50°C for 8 h, and the solid-liquid separation was performed to obtain modified carbon nanotubes.
[0179] (3) Preparation of elastic buffer particles
[0180] The operation is the same as step (3) of Example 6.
[0181] (4) Preparation of composite negative electrode materials
[0182] The elastic buffer particles were added to deionized water and ultrasonically dispersed for 10 min, and the pH value was adjusted to 7 to obtain a dispersion of elastic buffer particles with a concentration of 5 g / L. Polyvinyl pyrrolidone was added to the elastic buffer particle dispersion according to the mass ratio of the elastic buffer particles to polyvinyl pyrrolidone of 2:1 so that the concentration in the dispersion was 2.5 g / L, so that the polyvinyl pyrrolidone coated the elastic buffer particles, stirred for reaction for 24 h, and the solid-liquid separation was performed. The obtained solid phase was washed with deionized water, vacuum dried, loaded into a ceramic crucible and placed in a tubular furnace. Under the condition of continuous introduction of argon as a protective atmosphere, the temperature was increased from room temperature to 600 °C at a rate of 5 °C / min and kept at this temperature for 2 h for carbonization, and then cooled to room temperature with the furnace to obtain the obtained product.
[0183] Example 9
[0184] In this embodiment, the steps for preparing a silicon-carbon composite negative electrode material having an elastic buffer structure are as follows:
[0185] (1) Preparation of porous silicon / silicon dioxide particles
[0186] Ni-Si alloy particles with a Si content of 50 wt.% were placed in a muffle furnace, heated to 550 °C in an air atmosphere and kept at this temperature for 20 h for heat treatment, so that the iron element in the Ni-Si alloy particles was oxidized into nickel oxide, and the silicon on the surface of the Ni-Si alloy particles was oxidized into silicon dioxide. After being taken out and naturally cooled in the air, they were immersed in a sulfuric acid solution with a concentration of 10 wt.%, and corroded at room temperature for 10 h to remove the nickel oxide. The solid-liquid separation was carried out, and the obtained solid phase was repeatedly washed with deionized water and ethanol, vacuum dried, and fully ground to obtain porous silicon / silicon dioxide particles.
[0187] (2) Activation and modification treatment
[0188] The porous silicon / silicon dioxide particles were added to a CTAB aqueous solution with a concentration of 3.5 wt.%, stirred for reaction for 1 h, and the solid-liquid separation was performed. The obtained solid phase was repeatedly washed with deionized water and ethanol and dried to obtain activated porous silicon / silicon dioxide particles.
[0189] The carbon nanotubes were immersed in a mixture of HNO3 and H2SO4, wherein the concentration of HNO3 was 15 wt.%, and the concentration of H2SO4 was 30.0 wt.%, and the mixture was reacted in a water bath at 50°C for 15 h, and the solid-liquid separation was performed to obtain modified carbon nanotubes.
[0190] (3) Preparation of elastic buffer particles
[0191] The operation is the same as step (3) of Example 6.
[0192] (4) Preparation of composite negative electrode materials
[0193] The elastic buffer particles were added to deionized water and ultrasonically dispersed for 10 min, and the pH value was adjusted to 9 to obtain a dispersion of elastic buffer particles with a concentration of 5 g / L. According to the mass ratio of elastic buffer particles to polypyrrole of 10:1, polypyrrole was added to the dispersion of elastic buffer particles to make its concentration in the dispersion 0.5 g / L, and the reaction was stirred for 24 h to make polypyrrole coat the elastic buffer particles, and the solid-liquid separation was performed. The obtained solid phase was washed with deionized water, vacuum dried, loaded into a ceramic crucible and placed in a tubular furnace. Under the condition of continuous introduction of argon as a protective atmosphere, the temperature was increased from room temperature to 800 °C at a rate of 5 °C / min and kept at this temperature for 2 h for carbonization, and then cooled to room temperature with the furnace to obtain the obtained product.
[0194] The above embodiments are only some implementation methods of the present invention and are not intended to limit the present invention. Those skilled in the art can make non-essential adjustments such as equivalent replacement or change based on the technical concept and technical solution of the present invention. All equivalent replacements and non-essential adjustments should be included in the protection scope of the present invention.
Claims
1. A silicon-carbon composite negative electrode material with an elastic buffer structure, characterized in that: The composite negative electrode material is composed of porous silicon / silicon dioxide particles, a carbon nanotube elastic buffer layer and a coating layer. The porous silicon / silicon dioxide particles are composed of silicon particles and a silicon dioxide layer coating the silicon particles. The silicon / silicon dioxide particles have a uniform open nanoporous structure. The particle size of the silicon / silicon dioxide particles is in the micron level. The carbon nanotube elastic buffer layer is formed by modified carbon nanotubes that are mutually entangled and assembled. The carbon nanotube elastic buffer layer has a mutually interpenetrating nanopore structure. The thickness of the carbon nanotube elastic buffer layer is 100-300 nm. The surface of the modified carbon nanotube has hydroxyl and carboxyl functional groups. The coating layer is composed of carbon or nitrogen-doped carbon. The carbon nanotube elastic buffer layer coats the porous silicon / silicon dioxide particles. The elastic buffer layer can buffer the volume expansion of the porous silicon / silicon dioxide particles during lithium insertion / delithiation. The coating layer is coated outside the elastic buffer layer. The thickness of the coating layer is 4-50 nm. The preparation method of the composite negative electrode material comprises the following steps: (1) Preparation of porous silicon / silicon dioxide particles The micron-sized silicon alloy particles are heat-treated at 550-1100° C. in an air atmosphere, the metal elements in the silicon alloy particles are completely oxidized into metal oxides and the elemental silicon is replaced, and the elemental silicon generated on the surface of the particles is oxidized into silicon dioxide, the heat-treated silicon alloy particles are immersed in an acidic solution that does not react with elemental silicon, the metal oxides are corroded and removed to form a uniform open nanoporous structure, and the obtained solid phase is washed and dried to obtain porous silicon / silicon dioxide particles; the content of Si in the silicon alloy is 30 wt.%-70 wt.%, and the silicon alloy is a Mg-Si alloy, a Ni-Si alloy or a Fe-Si alloy; (2) Activation and modification treatment The porous silicon / silicon dioxide particles are added to a hexadecyltrimethylammonium bromide aqueous solution, stirred sufficiently, and the solid-liquid separation is performed, and the obtained solid phase is washed and dried to obtain activated porous silicon / silicon dioxide particles; Immerse the carbon nanotubes in a mixture of HNO3 and H2SO4, fully react at 50-100°C to form functional groups including hydroxyl and carboxyl groups on the surface of the carbon nanotubes, separate the solid and the liquid, and obtain modified carbon nanotubes; (3) Preparation of elastic buffer particles The activated porous silicon / silicon dioxide particles are fully dispersed in water and the pH value is adjusted to 1-5 to obtain dispersion A; the modified carbon nanotubes are added into water and stirred at a speed of 60-600 rpm for 0.3-3 h to pre-assemble the modified carbon nanotubes in water to form modified carbon nanotube aggregates to obtain dispersion B; the dispersion A is added dropwise into the dispersion B and stirred for 5-10 h to assemble the modified carbon nanotube aggregates on the surface of the activated porous silicon / silicon dioxide particles to form an elastic buffer layer, and the solid-liquid separation is performed to obtain elastic buffer particles; In this step, the amount of dispersion A and dispersion B is controlled so that the mass ratio of activated porous silicon / silicon dioxide particles to modified carbon nanotubes is (1-3): 1; the concentration of activated porous silicon / silicon dioxide particles in dispersion A is 2-6 g / L, and the concentration of modified carbon nanotubes in dispersion B is 1-5 g / L; (4) Preparation of composite negative electrode materials The elastic buffer particles are dispersed in water, and then monomers or polymer materials are added to form a reaction precursor solution. Reaction conditions are applied to polymerize the monomers and coat the surfaces of the elastic buffer particles, or to coat the surfaces of the elastic buffer particles with polymer materials. The solid-liquid separation is performed, and the obtained solid phase is washed and dried, and fully carbonized at 600-800°C under a protective gas atmosphere to obtain a composite negative electrode material.
2. The silicon-carbon composite negative electrode material with an elastic buffer structure according to claim 1, characterized in that: In the composite negative electrode material, the sum of the contents of the carbon nanotube elastic buffer layer and the coating layer is 20 wt.% to 40 wt.%, and the remainder is porous silicon / silicon dioxide particles.
3. The silicon-carbon composite negative electrode material with an elastic buffer structure according to claim 1 or 2, characterized in that: The particle size of the porous silicon / silicon dioxide particles is 1~30 μm, and the thickness of the silicon dioxide layer is 4~10 nm.
4. The silicon-carbon composite negative electrode material with an elastic buffer structure according to claim 1 or 2, characterized in that: The pore size distribution of the composite negative electrode material is between 1 and 150 nm.
5. The silicon-carbon composite negative electrode material with an elastic buffer structure according to claim 1, characterized in that: In the reaction precursor solution of step (4), the mass ratio of the elastic buffer particles to the monomer or polymer material is (2-100):
1.
6. The silicon-carbon composite negative electrode material with an elastic buffer structure according to claim 5, characterized in that: In step (4), the monomer is dopamine or phenolic resin, and the polymer material is polyvinyl pyrrolidone or polypyrrole.
7. The silicon-carbon composite negative electrode material with an elastic buffer structure according to claim 1, characterized in that: In step (2), the concentration of the hexadecyltrimethylammonium bromide aqueous solution is 1 wt.%~10 wt.%; in the mixed solution of HNO3 and H2SO4, the concentration of HNO3 is 15 wt.%~60 wt.%, and the concentration of H2SO4 is 5 wt.%~30 wt.%.
Citation Information
Patent Citations
Carbon-coated porous silicon-carbon composite material and preparation method thereof
CN111211314A